The unexpected surgical emergency in a child with cystic fibrosis: An acute appendicitis with unusual presentation - Doğan, Emrah; Süzen, Alev; Mouline Doğan, Marwa; Çelik, Serkan Yaşar; Çullu, Neşat (Journal of Surgery and Medicine, 2019)
Cystic fibrosis is an autosomal recessive disease characterized by structural and metabolic genetic dysfunction of the exocrine glands. Abdominal pain is the most common symptom in patients with cystic fibrosis within gastrointestinal symptoms. It is more commonly related to distal ileal obstruction syndrome. In patients with cystic fibrosis, the appendix is frequently distended due to an intense eosinophilic secretion but ironically, the incidence of acute appendicitis has been reported under the general population. Acute appendicitis in patients with cystic fibrosis commonly present with atypical symptoms. We present the case of cystic fibrosis with an acute appendicitis which had atypical radiologic and laboratory findings that were not compatible with the diagnosis. The diagnosis was made on the basis of clinical examination. As a result, it is of great importance to know that acute appendicitis in patients with cystic fibrosis can present with unusual clinical and radiological findings in order to avoid delayed diagnosis and related serious complications.